Xi-Modi Summit : Testing Their Political Will? - Suryanarayana, Pisupati Sadasiva (2020)
Chinese President Xi Jinping’s latest candid dialogue with Indian Prime Minister Narendra Modi at a historical site in India shows that the two wary Asian neighbours are testing their respective political will in the current uncertain global situation.